The Vlasiator 5.2 ionosphere – coupling a magnetospheric hybrid-Vlasov simulation with a height-integrated ionosphere model - U. Ganse; Y. Pfau-Kempf; H. Zhou; L. Juusola; L. Juusola; A. Workayehu; F. Kebede; K. Papadakis; M. Grandin; M. Alho; M. Battarbee; M. Dubart; et al. (Geoscientific Model Development)
Simulations of the coupled ionosphere–magnetosphere system are a key tool to understand geospace and its response to space weather. For the most part, they are based on fluid descriptions of plasma (magnetohydrodynamics, MHD) formalism, coupled to an electrostatic ionosphere. Kinetic approaches to modeling the global magnetosphere with a coupled ionosphere system are still a rarity.